Cities, states and the pandemic: challenges and opportunities for transnational city networks - Valeriani, M.; Marchetti, R.; Passalacqua, C. C. (Frontiers in Political Science, 2025)
The growing role of cities in today’s globalized world is well known. As a result of their central position in many positive and negative global dynamics, cities are receiving more and more attention in various fields of study, including international relations (IR). In this context, COVID-19 was a turning point that once again demonstrated the international activism of cities, offering valid patterns of crisis response and management as an alternative to those of central governments. By observing this increased activism, this study has identified three main ways in which cities have developed international initiatives through unilateral, bilateral or multilateral actions, such as transnational city networks (TCNs), which have been one of the main tools used by cities to support or bypass central governments. Against this background, this study also sought to explore the main conditions that are associated with specific TCNs in providing solutions to the needs of their member cities in a time of crisis such as the COVID-19 pandemic. It did so through a qualitative comparative analysis focusing on some of the key characteristics of TCNs: top-down vs. bottom-up networks, relationships with IOs, mission and scope. The results indicate the conditions under which specific TCNs emerge as effective tools for international urban activism.